Cancer burden in Japan based on the latest cancer statistics: need for evidence-based cancer control programs - Matsuda, Tomohiro; Saika, Kumiko (Annals of Cancer Epidemiology; Vol 2 (September 2018): Annals of Cancer Epidemiology, 2018)
Cancer as a cause of death has been constantly increasing in Japan, and it became the leading cause of death in 1981. As for incidence and survival, the research groups financed by the Health, Labour and Welfare Ministry have estimated the national cancer incidence in Japan based on high-quality data from several cancer registries over a long period. With the enactment of the Act on Promotion of Cancer Registries in 2013, cancer became a reportable disease; this allows us to establish a cancer control program based on reliable statistics. Cancer mortality and incidence in 2014 describe the cancer burden in the country precisely. Age-standardized mortality rates (world population) for males and females were 114.8 and 63.0/100,000, respectively. Age-standardized incidence rates for males and females were 303.1 and 224.8/100,000, respectively. According to the results of an international collaborative study, CONCORD-3, Japan demonstrated good results, such as net survival of 60.3% for stomach cancer. The 5-year prevalence for all cancers was 1,734,060 in males and 1,399,380 in females. The recent trends of cancer mortality and incidence showed that no increase of mortality was observed in any primary sites in males. However in females, uterine cancer, both of the cervix and the uterine body, showed increasing mortality. Mortality in all the other primary sites is decreasing or at least leveling off. As for incidence, cancers of the pancreas, prostate, and thyroid and malignant lymphoma were increasing in males, and cancers of the esophagus, colon and rectum, lung, breast, uterus, ovary, and thyroid and malignant lymphoma were increasing in females. Geographical disparities at these sites were associated with well-known risk factors, such as smoking, salt intake, hepatitis C virus infection, and Helicobacter pylori infection. Given its hyper-aging society, Japan will likely face a substantial increase in the number of elderly cancer patients. This heavy cancer burden will be compounded by the functional limitations and co-morbidities that often present in older cancer patients. Cancer statistics and cancer registration in Japan in accordance with legislation are the keys to performing effective evidence-based cancer control.